"Separated during the first hours"-Postnatal care for women and newborns during the COVID-19 pandemic: A mixed-methods cross-sectional study from a global online survey of maternal and newborn healthcare providers. - Aline Semaan; Teesta Dey; Amani Kikula; Anteneh Asefa; Thérèse Delvaux; Etienne V Langlois; Thomas van den Akker; Lenka Benova (Public Library of Science (PLoS), 2022)
Routine postnatal care (PNC) allows monitoring, early detection and management of complications, and counselling to ensure immediate and long-term wellbeing of mothers and newborns; yet effective coverage is sub-optimal globally. The COVID-19 pandemic disrupted availability and quality of maternal and newborn care despite established guidelines promoting continuity of essential services. We conducted a cross-sectional global online survey of 424 maternal and newborn healthcare providers from 61 countries, to explore PNC provision, availability, content and quality following the early phase of the COVID-19 pandemic. The questionnaire (11 languages), included four multiple-choice and four open-text questions on changes to PNC during the pandemic. Quantitative and qualitative responses received between July and December 2020 were analysed separately and integrated during reporting. Tightened rules for visiting postpartum women were reported in health facilities, ranging from shorter visiting hours to banning supportive companions and visitors. A quarter (26%) of respondents reported that mothers suspected/confirmed with COVID-19 were routinely separated from their newborns. Early initiation of breastfeeding was delayed due to waiting for maternal SARS-CoV-2 test results. Reduced provision of breastfeeding support was reported by 40% of respondents in high-income countries and 7% in low-income countries. Almost 60% reported that women were discharged earlier than usual and 27% perceived a reduction in attendance to outpatient PNC. Telemedicine and home visits were mostly reported in high-income countries to ensure safe care provision. Beyond the early phase of the COVID-19 pandemic, severe disruptions to content and quality of PNC continued to exist, whereas disruptions in availability and use were less commonly reported. Depriving women of support, reducing availability of PNC services, and mother-newborn separation could lead to negative long-term outcomes for women, newborns and families, and deny their rights to respectful care. Protecting these essential services is imperative to promoting quality woman-centred PNC during and beyond the pandemic.